Tren Riset Tentang Kepemimpinan pada Jurnal Administrasi di Indonesia: Tinjauan Literatur Sistematis - I Gde Eka Sukarma Putra; Pantius Drahen Soeling (Dinasti Review, 2024)
There has been quite a lot of research discussing leadership in Indonesia, especially in the context of administrative management, both in the public and private sectors. However, not many have studied/reviewed the information presented in these studies. This research aims to determine research trends in leadership in the SINTA-indexed administrative journal in Indonesia from 2004 to 2023. The method used is a systematic literature review. A literature review was carried out on 170 leadership journal articles indexed by SINTA 1-6. Based on the results of the study, it was concluded that there is a trend of increasing the number of research on leadership in administrative journals indexed by SINTA from 2004 to 2023. Quantitative research is the most dominant type of research. Public sector workers are most often the subjects of research on leadership. Leadership in general is the most frequently researched topic. Questionnaires are the most frequently used data collection instrument and regression analysis techniques are the most frequently used as analysis techniques.